Analisis Kompetensi Pustakawan dalam Penerapan Teknologi Informasi dan Komunikasi di Perpustakaan Khusus Kementerian/Lembaga - Lidya Wahyu Sari; Zulva Ibadati (Media Pustakawan, 2023)
The role of adaptive librarians affects the implementation of Information and Communication Technology (ICT), especially in governmental libraries. It adjusts the competencies and abilities needed by librarians. Therefore, librarians are required to rebuild and improve their skills related to ICT. In Indonesia, Standar Kompetensi Kerja Nasional Indonesia (SKKNI) 2019 is used as a national education & training framework for librarians. To explore this theme according to SKKNI, a sequential exploratory research was conducted with contributions from librarians and/or library staff who work in governmental libraries across the Republic of Indonesia. Through in-depth interviews, focused group discussions with 28 librarians from 14 governmental libraries in Jabodetabek, also an online survey (74 respondents), the researchers were able to gain a pattern that showed the tendency of higher ability level in the competency units related to ICT utilization in the library than the competency units in developing library information systems. The unit of competence with the highest mean score is the unit of competence related to multimedia production, including the management of the library’s social media content. Aligning with this result, National Library as the central supervisor for the librarian needs to collaborate with related stakeholders, especially in accommodating competence development efforts to build a national digital ecosystem. Those efforts include the formulation of continuing development program -gradual education and training program. Through this collaboration between various stakeholders, the development of librarian competencies specifically within governmental libraries can be carried out efficiently, following the real needs in the field.